Investment decisions for Indonesian workers: case study of migrant workers in Joho Village, Tulungagung Regency - Himmati, Risdiana; Rani, Pranitya Septiya (Fakultas Ekonomi dan Bisnis Islam UIN Salatiga, 2023)
This research aims to determine the factors that influence investment decisions for foreign workers in Joho Village, Kalidawir District, Tulungagung Regency. The population is 200 people, and the sample taken in this research was 30 by direct interview. This research uses a quantitative approach with an associative research type and a sampling method using simple random sampling or random sampling. The data management tool used in this research is the SPSS 20 application with binary logistic regression analysis. The variables used in this research consist of seven variables, namely gender, age, education, number of dependents, destination country, length of work, and income. The research results show that gender does not influence investment decisions for foreign workers in Joho Village. Age does not influence investment decisions for foreign workers in Joho Village. Education does not influence investment decisions for foreign workers in Joho Village. The number of dependents does not influence investment decisions for foreign workers in Joho Village. The destination country does not influence TKI's investment decisions in Joho Village and income does not influence TKI's investment decisions in Joho Village.